2014
DOI: 10.1080/19315864.2014.920941
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Adaptive Functioning in Adolescents With Down Syndrome: Specifying Targets for Intervention

Abstract: Background Research suggests that adolescents with Down syndrome experience increased behavior problems as compared to age matched peers; however, few studies have examined how these problems relate to adaptive functioning. The primary aim of this study was to characterize behavior in a sample of adolescents with Down syndrome using two widely-used caregiver reports: the Behavioral Assessment System for Children, 2nd Edition (BASC-2) and Child Behavioral Checklist (CBCL). The clinical utility of the BASC-2 as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Furthermore, because STM and WM processes require interaction between cortical regions and the hippocampus ([ 77 80 ]), behavioral data suggest impairment in connectivity among neural regions in DS. Past research has shown unique patterns of neural activity in children with DS and, in particular, under-connectivity between distant neural regions in those with DS compared to TD controls [ 6 , 138 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, because STM and WM processes require interaction between cortical regions and the hippocampus ([ 77 80 ]), behavioral data suggest impairment in connectivity among neural regions in DS. Past research has shown unique patterns of neural activity in children with DS and, in particular, under-connectivity between distant neural regions in those with DS compared to TD controls [ 6 , 138 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although research has consistently documented adaptive function deficits in individuals with DS [ 5 , 6 , 144 ], research examining the relation between memory and adaptive function remains very limited. The two studies examining this relationship found that LTM performance is predictive of adaptive function in teens with DS, after accounting for age [ 9 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing literature has been mixed with regard to these latter domains. Although several studies have pointed to sex-differences in pragmatics, behavior, and communication skills (Lund, 1988 ; Berglund et al, 2001 ; Määttä et al, 2006 ; Van Gameren-Oosterom et al, 2011 ; de Sola et al, 2015 ; Lee et al, 2017 ), studies focused on the adolescent period specifically have generally shown no sex differences with regard to pragmatics (Martin et al, 2017 ) or behavior (Jacola et al, 2014 ). Taken together, these results suggest that sex differences in DS may vary as a function of chronological age and developmental level and, perhaps, the context of assessment.…”
Section: Discussionmentioning
confidence: 99%
“…As individuals get older, those externalizing behaviors tend to decline, whereas increased internalizing symptoms (e.g., social withdrawal, depression, anxiety, secretive behavior) are more likely to occur (Grieco et al, 2015 ). Finally, within DS, there is some, albeit inconsistent evidence, of sex differences with regard to behavioral difficulties; indeed, some studies have suggested increased behavior problems in males (Van Gameren-Oosterom et al, 2011 , 2013 ), whereas others have reported increased problems in females (Dykens et al, 2002 ), and still others have found no differences (Jacola et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%